SYNCHRONIZATION OF OVULATION USING DOUBLESYNCH PROTOCOL IN CROSSBRED CATTLE UNDER FIELD CONDITIONS - NAVAMANI, K; KULASEKAR, K; KRISHNAKUMAR, K; RADHAKRISHANAN, L (The Indian Journal of Animal Reproduction, 2022)
The crossbred cattle (n=110) were randomly divided to receive either no treatment and were regular cycling(group 1, n=10), and the remaining (group II, n=100) were pubertal heifers, repeat breeders and anestrous. Theanimals were fed area specific mineral mixture @ 30 gm/d/animal for 45d and group II animals were subjectedto doublesynch protocol followed by FTAI. Body condition scores (BCS) was accessed and ranged 2.4-3.4 in allthe animals. Blood samples was collected for the estimation of plasma Beta hydroxy butyric acid (BHBA) andthe animals that failed to conceive to doublesynch had higher plasma BHBA. The conception rate was 54% insynchronized compared to 40% in control group. Thus, doublesynch is a useful protocol to improve the conceptionrate in infertile cattle under field condition.
Keywords: BHBA; Conception; Crossbred cattle; Doublesynch; Hormone